ANALISIS HUKUM PENGENAAAN PAJAK TERHADAP PERMOHONAN HAK ATAS TANAH PERTAMA KALI DAN PENDAFTARANNYA DI KOTA MEDAN - EFENDI EFENDI (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhammad Yamin2. Bastari3. T. Keizerina Devi A The first application of the registration of land title may or may not be encouraged by the transfer of the rights over the land. This research is entitled “A Legal Analysis of Tax Charge to the First Application of Land Title and Its Registration in Medan.” The research problems are what taxes are charged to the first application of land title and it registration in Medan and how the justice principle is fulfilled in the provisions of tax charge to the first application of land title and its registration in Medan. This is a normative legal research which is analytical descriptive. It uses secondary data consisting of primary data such as the Law No. 36/2008 on Income Tax and the Law No. 28/2009 on PDRD (Regional House of Representatives) and the regulations related to the laws, secondary legal materials such as books and tertiary legal materials such as general dictionaries and legal dictionaries.Keyword: Tax, Land Title Regisration, Medan